KAJIAN SOSIAL EKONOMI PETANI CAP TIKUS DI DESA WUWUK KECAMATAN TARERAN KABUPATEN MINAHASA SELATAN - Wuisan, Miranti Friyana; Kaihatu, Jolanda Esther; Poli, Ellen Eva; Selvana Treny Rosita Tewal; Erick Lobja; Cahya Gumilang (Fakultas Ilmu Sosial dan Hukum, 2025)
This study aims to determine the socio-economic study of cap tikus farmers in Wuwuk Village, Tareran District, South Minahasa Regency. This study uses a qualitative descriptive method. Data collection techniques used are observation, interviews, documentation. The results of the study indicate that: 1) The level of education of cap tikus farmers in Wuwuk Village is in the middle category. 2) The income of cap tikus farmers is an average of IDR 4,000,000/month, with the highest income of IDR 6,000,000/month and the lowest IDR 2,700,000/month 3) The level of consumption or expenditure of cap tikus farmers per month is at least around IDR 3,000,000 and at most IDR 7,000,000, which is for daily needs. 4) Ownership of assets or land used by farmers for processing cap tikus still uses land owned by other people. 5) Farmers' access to the cap tikus processing site is poor because of uneven development, in this case some roads are already concrete and some are still dirt. 6) Marketing of captikus in Wuwuk Village is still limited because farmers only sell cap tikus to collectors and some of them sell retail at their homes.